The Russian Intervention in Syria - Iman Abdulwahid Majeed (American Journal of Economics and Business Management, 2023)
The subject of this research is "The Russian Intervention in Syria: Motives and Implications." It examines Russia's position on the Syrian revolution and their political support for Syria, with a focus on their military help and their support for a political solution to the Syrian chemical weapons problem. The study takes into account the viewpoint of international relations and looks at the mechanisms and circumstances surrounding the Russian political decision-makers in order to understand the motivations, factors, and interests that drove Russia's intervention in Syria and its impact on shifting the balance of power in the Syrian crisis.With an emphasis on the choice to intervene militarily and its results on the ground, the study focuses on the military and political ramifications of the operation. It emphasizes that the goal of the Russian involvement was to demonstrate Russia's new status as a major player on the world stage, posing a threat to American power and defending Russian interests in the Middle East and the Mediterranean.The study's analysis of the actual military actions in Syria reveals that Russia outperformed its initial objectives in Syria.